The Fish in School Meals pilot report - Bonis-Profumo, Gianna; Gomes, Silvino; Tilman, Emilio; Pereira, Angelo; De Jesus, Lucas Soares; Duarte, Agustinha; Simões, Noviana; Pires, Natalina; Pereira, Mario; Teoh, Shwu Jiau; Bhujel, Ram C.; Klumpyan, Katherine; et al. (WorldFish, 2024)
This report documents the design, implementation and evaluation of the Fish in School Meals pilot and provides recommendations for scaling up fish supply to schools in Timor-Leste. The pilot fits within pillar 3 - increased consumption activities of the Partnership for Aquaculture Development in Timor-Leste Phase 2 (PADTL2) project in partnership with key government stakeholders. It aims to establish and test systems to supply fresh tilapia to schools and assess its future scalability while helping to boost fish consumption among school-aged children in rural areas. As part of the national school meal program, Programa Merenda Eskolár (PME), the pilot supplied locally produced and genetically improved farmed tilapia (GIFT) to 10 schools in Ermera municipality. Over 1000 students from five preschools and five primary schools in rural and remote areas received a nutritious fish dish once a week, between July and November 2023. Ermera has some of the highest child malnutrition rates in the country, and it is a land-locked municipality with limited opportunities to access fresh fish. During the pilot, close to 10,000 meals with fish were served and over 2 t of tilapia supplied.